Dealing Chronic Diseases with Homoeopathy - Tripathy, Dr. Tridibesh; Shankar Das, Professor; Dharmendra Pratap Singh, Professor; Prusty, Dr. Umakant; Krushna Pattanaik, Dr. Jeevan; Bihary Pradhan, Dr. Pramod; Dubey, Mr. Anil; Kumar, Mr. Anjani; Tripathy, Ms. Sanskriti; Tripathy, Mrs. Anjali; Dwivedi, Prof. Rakesh; Gautam, Dr. Mohini (Clinical Medicine And Health Research Journal, 2023)
Since the time homoeopathy was introduced to the world in 1790 by Dr. Samuel Hahnemann, homoeopathy is popular for treating chronic diseases. When that was the case in late 18th, 19th & 20th century, homoeopathy was dealing with chronic diseases that were morbid but not mortal. In 21st century, after the epidemiologic transition, the chronic diseases have taken the form of Non-Communicable Diseases (NCD). [2, 15] 'These NCDs have not only morbidity but also high mortality'. The most hostile chronic diseases like diabetes, heart disease & cancer affects our health & reduces life expectancy. Conditions like heart disease, stroke, cancer, chronic respiratory diseases & diabetes are leading causes of death worldwide. These chronic diseases can affect viral organs like heart, lungs, kidneys & liver causing damage & impacting overall health & longevity & can lead to complications. [1, 2, 15] The article looks at the role of homoeopathy in dealing with the chronic diseases. It brings out the fact that homoeopathy can deal with not only treating these diseases but also prevent this diseases & promote health. The properties of homoeopathic medicines that are aligned to the essential medicines are also discussed. Finally, it mentions that these diseases can only be dealt only if Universal Health Coverage (UHC) is achievable. Achievability of UHC is only possible if the AYUSH systems are integrated into the mainstream & homoeopathy is an active component of this package. [12, 16, 17]